Effect of water content on the gelatinisation temperature of sago starch - Maaruf, A.G; Che Man, Y.B; Asbi, B.A; Junainah, A.H; Kennedy, J.F (Elsevier, 2001)
Differential scanning calorimetry (DSC) has been used to study gelatinisation phenomena of sago starch. Two endothermic transitions were observed for starch heated in the presence of a limited amount of water These transitions appear to be due to co-operative effects of water-mediated melting of starch crystallites, remaining crystallites and/or amylopectin crystallites. At a water content of 50%, evidence of M1 endotherm was observed and 85°C represents the effective Tm at the end of melting of native sago starch. The effect of starch concentration on the shape of these two endotherms was studied for sago starch. The experimental data were treated thermodynamically by applying equations describing phase transition of semi-crystalline polymers. The T0m value obtained by extrapolation to v1=0 was 390.6 K for sago.